Topological phases of matter : new particles, phenomena and ordering principles - Moessner, Roderich; Moore, Joel E. (Cambridge: Cambridge University Press, 2021)
"Topological concepts are essential to understand many of the most important recent discoveries in the basic physics of solids. Topology can be loosely defined as the branch of mathematics studying the properties of an object that are invariant under smooth distortions. Topological phases, as a result, show a kind of robustness and universality that is similar in spirit to the famous universality observed at continuous phase transitions, but with a very different microscopic origin. This chapter introduces some of the key examples of topological phases of matter and places them in the broader context of many-body physics. Einstein famously commented that statistical mechanics was one kind of physics whose basic principles would last forever, because they were based only on the assumption that our knowledge of a complex system is incomplete. Topological phases show how a kind of macroscopic simplicity and perfection can nevertheless emerge in many-particle systems, even in the presence of disorder and fluctuations that make a complete microscopic description impossible"--
Basic concepts of topology and condensed matter -- Integer topological phases -- Geometry and topology of wavefunctions in crystals -- Hydrogen atoms for fractionalisation -- Gauge and topological field theories -- Topology in gapless matter -- Disorder and defects in topological phases -- Topological quantum computation via non-Abelian statistics -- Topology out of equilibrium -- Symmetry, topology, and information.
Includes bibliographical references and index.
Keywords: Condensed matter; Topology; Topological defects (Physics); Geometric quantum phases